Dual-band LFM-CW Radar Scheme Based on Photonic Stretch Processing - CAO Jiming; LI Ruoming; YANG Jiyao; SUN Qiang; LI Wangzhe (Leida xuebao, 2019)
A dual-band LFM-CW radar scheme which is based on photonic stretch processing is proposed. The receiver which is based on a photonic frequency down-converter is able to receive the radar echoes of two bands with a single hardware. A dual polarization quadrature phase shift keying modulator is employed to implement the modulation scheme. The reference signals and echoes of two bands are modulated to orthogonally polarized light waves and sent to a Pol-demux coherent receiver through an amplifier and a filter, respectively, to perform stretch processing. In the transmitter, the reference and transmitted LFM signals with high frequency and wide bandwidth are generated by a photonic-assisted frequency multiplication module. Meanwhile, the generated signal is delayed before transmission. Thus, at the output of the coherent receiver, IF signals corresponding to two bands can be separated in the frequency domain. An experimental system operating in Cand Ku-bands with transmitting signal bandwidths of 1 and 2 GHz, respectively, is demonstrated and evaluated via a series of inverse synthetic aperture radar imaging tests, and the sampling rate of analog to digital converters is 100 MSa/s. The results show that the microwave photonics technology can provide solutions for receiving dual-band signal with a single hardware platform.